The island rule of body size demonstrated on individual hosts: phytophagous click beetle species grow larger and predators smaller on phylogenetically isolated trees. (11th February 2016) - Molleman, Freerk; Depoilly, Alexandre; Vernon, Philippe; Müller, Jörg; Bailey, Richard; Jarzabek‐Müller, Andrea; Prinzing, Andreas
Abstract: Aim: Under spatial isolation on oceanic islands, species tend to show extreme body sizes. From the point of view of many colonizers, individual hosts surrounded by phylogenetically distant neighbours are phylogenetically isolated. This study addresses for the first time how phylogenetic isolation of individual hosts affects body size of colonizers, and whether effects on body size reflect selection among colonizers established on host individuals rather than selection among colonizers dispersing toward trees or phenotypic plasticity of colonizers. Location: Rennes National Forest, Western France. Methods: We sampled click beetles (Elateridae) on individual oak trees varying in phylogenetic isolation from their neighbours and in age. We measured body size and fluctuating asymmetry (which we found to correlate to reduced body size) and related both to phylogenetic isolation and age of trees. We compared these relationships among species of different larval trophic position and adult body size, using meta‐analytical approaches. Results: Within species, body size changes with phylogenetic isolation of individual host trees: root feeders tend to become larger, predators smaller. Effects were independent of mean body‐size, disappeared with tree age, and were inconsistent with patterns of fluctuating asymmetry. Main conclusions: Our results are consistent with body‐size selection among colonizers established on individual trees, rather than selection among colonizers dispersing toward trees or phenotypic plasticity. Overall, phenotype patterns of animals across islands in the ocean may resemble those across host individuals in a phylogenetically distant neighbourhood, suggesting micro‐evolution of colonizers in response to the macro‐evolutionary structure of the host community.